Green Hydrogen Production by Photovoltaic-Assisted Alkaline Water Electrolysis: A Review on the Conceptualization and Advancements - Valdivia-Lefort, P (Elsevier Ltd, 2025)
The process of producing hydrogen by water electrolysis is becoming more and more popular as people look for clean and renewable energy sources. The alkaline electrolyzers show promising features, however, there is a room for improvement in the efficiency and energy usage. The research explores optimizing PV-assisted alkaline electrolysis setup to enhance the performance and reduce its energy input. The factors such as solar irradiation, electrolyzer design, catalysts, and operational parameters impacts the energy efficiency and hydrogen production rates. The strategies include coupling PV arrays and electrolyzers with DC/DC converters with MPPT to maximize power output. Thus, the underlying goal of the review is to present the strategies that can be applied to improve the process by considering the several operational conditions of the electrolyzer, which influence the gas quality and the energy efficiency. Further, the strategies to overcome the existing issues like variables over time, the effects of fluctuations in current, and the partial load operation of the electrical energy from the renewable sources are discussed. The advancements in the alkaline electrolyzer technology and their economic assessment and the energy efficiency of the for the hydrogen production are also addressed. As a conclusive remarks, the challenges and future perspectives of the PV-assisted alkaline water electrolyzer technology has been emphasized. © 2024 Hydrogen Energy Publications LLC